2001
DOI: 10.1038/sj.onc.1204841
|View full text |Cite
|
Sign up to set email alerts
|

The role of ceramide in receptor- and stress-induced apoptosis studied in acidic ceramidase-deficient Farber disease cells

Abstract: The activation of sphingomyelinases leading to the generation of ceramide has been implicated in various apoptotic pathways. However, the role of ceramide as an essential death mediator remains highly controversial. In the present study, we investigated the functional relevance of ceramide in a genetic model by using primary cells from a Farber disease patient. These cells accumulate ceramide as the result of an inherited deficiency of acidic ceramidase. We demonstrate that Farber disease lymphocytes and fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…Although our data are in agreement with previous findings using B13 (Selzner et al, 2001;Ogretmen and Hannun, 2004) or NOE (Hara et al, 2004) to block CDases, it has been reported that primary human SV-40 transformed skin fibroblasts or lymphocytes from Farber disease patients, a genetic disorder characterized by a decrease in acid CDase, were as sensitive to DNRinduced cell death as cells from healthy controls (Burek et al, 2001). This reported discrepancy with our findings might well be owing to the tumor specificity or type of cells used.…”
Section: Discussionsupporting
confidence: 94%
“…Although our data are in agreement with previous findings using B13 (Selzner et al, 2001;Ogretmen and Hannun, 2004) or NOE (Hara et al, 2004) to block CDases, it has been reported that primary human SV-40 transformed skin fibroblasts or lymphocytes from Farber disease patients, a genetic disorder characterized by a decrease in acid CDase, were as sensitive to DNRinduced cell death as cells from healthy controls (Burek et al, 2001). This reported discrepancy with our findings might well be owing to the tumor specificity or type of cells used.…”
Section: Discussionsupporting
confidence: 94%
“…Accordingly, sensitivity toward ceramide-induced apoptosis was recently reported to differ between different cell types. In these studies, similar to our observation, tumor cells glare to be more sensitive toward ceramide-induced apoptosis as compared with primary cells (57,58).…”
Section: Discussionsupporting
confidence: 78%
“…In fact, the overexpression of acid ceramidase protects fibroblasts from tumor necrosis factor (TNF)-induced ceramide accumulation and cell death [20], and the fibroblasts of Farber's disease patients, which have an inherited deficiency in acidic ceramidase, are more sensitive to ceramide-induced cell death [29]. The role of sphingosine kinases in cell survival and transformation has been investigated extensively [19,30].…”
Section: Discussionmentioning
confidence: 99%